Masterpiece - Broach, Elise (Broach, Elise. Masterpiece adventures, 2008)
After Marvin, a beetle, makes a miniature drawing as an eleventh birthday gift for James, a human with whom he shares a house, the two new friends work together to help recover a Durer drawing stolen from the Metropolitan Museum of Art.